PERBEDAAN HASIL HITUNG BERBAGAI JENIS LEUKOSIT PADA PASIEN COVID-19 YANG ISOLASI MANDIRI DENGAN ISOLASI DI RSUD KABUPATEN MELAWI - Nur Reza; Edi Santoso; Ari Nuswantoro; Ratih Indrawati; Etiek Nurhayati; Aditia Aditia (Poltekkes Kemenkes Bandung, 2022)
COVID-19 infection causes various clinical manifestations so the treatment method is also different for each individual. Patient isolation is one of the treatments to break the chain of transmission of COVID-19. Asymptomatic to moderate symptomatic patients are usually asked to self-isolate, while those with severe and critical symptoms are isolated in hospital. Leukocyte examination is an important parameter and plays a role in determining patient follow-up. The aim of this study was to find out whether there were differences in leukocyte differential-counts in COVID-19 patients who were self-isolating and those isolated at Melawi Regional Hospital. This study had a cross-sectional design by taking data from medical records of COVID-19 patients at Melawi Regional Hospital during October 2021 to July 2022. The data taken were from 399 COVID-19 patients, consisting of 182 patients are self-isolating and 217 patients are isolating at Melawi Regional Hospital. In self-isolated patients, the average value of leukocyte count was 7.04 x 10³ cells/µL, and the leukocyte differential-counts was neutrophils 58.45%, lymphocytes 21.81%, monocytes 13.84%, eosinophils 1.52%, and basophils 4.38%. In isolated patients at Melawi Regional Hospital, the average value of leukocyte count was 9.89 x 10³ cells/µL, and the leukocyte differential-counts was neutrophils 75.09%, lymphocytes 12.97%, monocytes 8.38%, eosinophils 0.46%, and basophils 3.11%. The Mann-Whitney U test obtained a significance value of 0.000 (p < 0.05), which means there is a significant difference in the results of leukocyte counts between self-isolated patients and those isolated at Melawi Regional Hospital.